Development and validation of a novel non‐contact monitor of nocturnal respiration for identifying sleep‐disordered breathing in patients with heart failure. (1st March 2016) - Savage, Henry Oluwasefunmi; Khushaba, Rami N.; Zaffaroni, Alberto; Colefax, Michael; Farrugia, Steven; Schindhelm, Klaus; Teschler, Helmut; Weinreich, Gerhard; Grueger, Hartmut; Neddermann, Martina; Heneghan, Conor; Simonds, Anita; et al.
Abstract: Aims: At least 50% of patients with heart failure (HF) may have sleep‐disordered breathing (SDB). Overnight in‐hospital polysomnography (PSG) is considered the gold standard for diagnosis, but a lack of access to such testing contributes to under‐diagnosis of SDB. Therefore, there is a need for simple and reliable validated methods to aid diagnosis in patients with HF. The aim of this study was to investigate the accuracy of a non‐contact type IV screening device, SleepMinder TM (SM), compared with in‐hospital PSG for detecting SDB in patients with HF. Methods and results: The study included 75 adult patients with systolic HF and suspected SDB who underwent simultaneous PSG and SM recordings. An algorithm was developed from the SM signals, using digital signal processing and pattern recognition techniques to calculate the SM apnoea‐hypopnoea index (AHI). This was then compared with expert‐scored PSGAHI . The SM algorithm had 70% sensitivity and 89% specificity for identifying patients with clinically significant SDB (AHI ≥ 15/h). At this threshold, it had a positive likelihood ratio of 6.3 and a negative likelihood ratio of 0.16. The overall accuracy of the SMAHI algorithm was 85.8% as shown by the area under a receiver operator characteristic curve. The mean AHI with SM was 3.8/h (95% confidence interval 0.5–7.1) lower than that with PSG. Conclusions: The accuracy of the non‐contact type IV screening device SM is good for clinically significant SDB in patients with systolic HF and could be considered as a simple first step in the diagnostic pathway.